Predictors of First Ambulation During Hospitalization Among Patients Admitted For Acute Myocardial Infarction - Ferreira, Olga Lucia Cortés (My University, 2009)
Purpose: To determine the timing of first ambulation during hospitalization among patients admitted for acute myocardial infarction (AMI) and to identify the predictors of first ambulation. Methods: This retrospective cohort study included 500 AMI patients admitted during 2004 to one of three hospitals that form the Hamilton Health Sciences Corporation in Hamilton, Ontario, Canada. The patients were randomly selected from a total of 1,014 charts from the Hamilton Health Sciences Computerized Health Records (SOVERA). Using a chart abstraction tool, the following data were collected from each patient's chart: demographic information, past medical history, treatment, complications, and patterns of ambulation while in hospital. The primary outcome was first ambulation, defined as the first time patients walked during their hospital stay. Secondary outcomes included heart rate at discharge and mortality during hospitalization. The relationship between patient and care-related factors and the time of first ambulation after AMI was explored through a time to event analysis using Cox regression; the associations were expressed as hazard ratios. The fit for the proportional hazard model was assessed and a stratified proportional hazard model was performed for age. Results: Of the 500 charts, 60 were excluded. Of the 440 patients who were included in the final analysis, 340 (77.3%) walked during hospitalization. One hundred fifteen (26.1 %) walked during the first 48 hours (early walking), 98 (22.3%) walked between 49-96 hours (intermediate walking), and 127 (28.9%) walked after 96 hours (late walking). A total of 100 patients (22.7%) were categorized as non-walkers. Factors that emerged in the survival analysis that were positively associated with early ambulation after AMI and that proved the proportionality on the assessment of the fit of the model were: having a family history of cardiovascular disease (HR 1.33; 95% Cl 1.00, 1.44; p=0.05), receiving thrombolysis (HR 1.47; 95% Cl 1.11, 1.49; p=0.007), receiving nitroglycerin (HR 1.51; 95% Cl 1.19, 1.93; p<0.001 ), and taking calcium channel blockers (HR 1.58; 95% Cl 1.22, 2.05; p<0.001 ). Factors that were negatively associated with early ambulation after AMI were age >59 years (HR 0.98; 95% Cl 0.97, 0.99; p<0.001 ), having an arrhythmia in-hospital (HR 0.48; 95% Cl 0.22, 0.94; p=0.04), taking inotropic drugs (HR 0.72; 95% Cl 0.53, 0.98; p<0.001 ), and undergoing coronary artery bypass surgery (HR 0.51; 95% Cl 0.33, 0.78; p=0.002). Conclusion: There is variability in the timing of first ambulation among patients hospitalized with an AMI. Furthermore, those who walked early were more likely to have a family history of cardiovascular disease, have received thrombolysis, and be taking nitroglycerin or calcium channel blockers. Those least likely to walk early were older (>59 years), were more likely to have had an arrhythmia inhospital, to be taking inotropic drugs, and to have undergone coronary artery bypass surgery.
Keywords: acute myocardial infarction; timing of first ambulation; predictors of first ambulation; retrospective cohort study; Hamilton Health Sciences; patient and care related factors